Analisis Intensitas Bunyi Yang Dihasilkan Oleh Mesin Kapal Penyebrangan Dengan Aplikasi Sound Level Meter - Alfarizi Alfarizi; Pujianti Bejahida Donuata; Erwin Prasetyo; Adi Jufriansah (Kappa Journal, 2022)
The impact of high-intensity noise can cause discomfort for crew and ship passengers. The noise is partly caused by the maine engine which is the biggest noise source. So it is necessary to find a solution on how to reduce noise and the impact of the noise. The purpose of this study was to determine the magnitude of the sound intensity and the effect of sound intensity on the comfort of the crew and passengers. The research was conducted using the Sound Level Meter (SLM) application. Measurements made in the passenger compartment and an average of 66.4 dB to 73.6 dB indicate that the ship's engine noise level when operating is included in the strong category according to Suma'mur's study, 2009, but does not cause deafness and hearing damage.